Canopy Apparent Photosynthetic Characteristics and Yield of Two Spike-Type Wheat Cultivars in Response to Row Spacing under High Plant Density - Liu, Tiening (PLoS One, 2016)
In northern China, large-spike wheat (Triticum aestivum L) is considered to have significant potential for increasing yields due to its greater single-plant productivity despite its lower percentage of effective tillers, and increasing the plant density is an effective means of achieving a higher grain yield. However, with increases in plant density, the amount of solar radiation intercepted by lower strata leaves is decreased and the rate of leaf senescence is accelerated. Row spacing can be manipulated to optimize the plant spatial distribution under high plant density, therefore improving light conditions within the canopy. Consequently, field experiments were conducted from 2010 to 2012 to investigate whether changes in row spacing under high plant density led to differences in canopy apparent photosynthesis (CAP), individual leaf photosynthesis and grain yield. Two different spike-type winter wheat cultivars, Jimai22 (a small-spike cultivar as a control cultivar) and Wennong6 (a large-spike cultivar), were grown at a constant plant density of 3,600,000 plants ha(–1) (a relatively higher plant density) over a wide range of row spacing as follows: 5-cm row spacing (R(0)), 15-cm row spacing (R(1)), 25-cm conventional row spacing (R(2)), and 35-cm row spacing (R(3)). The two-year investigations revealed that increased row spacing exhibited a significantly higher light transmission ratio (LT), which improved light conditions within the canopy; however, excessive light leakage losses in R(2) and R(3) treatments were not favorable to improved irradiation energy utilization efficiency. Aboveground biomass accumulation was influenced by row spacing. Two spike-type wheat accumulated greater biomass under 15-cm row spacing compared to other row spacing treatments, although a markedly improved photosynthetic rate (P(N)), effective quantum yield of photosystem II (Φ(PSII)) and maximal efficiency of photosystem II photochemistry (F(v)/F(m)) in the penultimate and third leaves were observed in R(2) and R(3) treatments. At the same time, a longer duration of CAP and green leaf area was maintained in R(1) during grain filling. Compared with conventional row spacing, Wennong6 in R(1) treatment obtained 21.0% and 19.1% higher grain yield in 2011 and 2012, respectively, while for Jimai22 it increased by 11.3% and 11.4%, respectively. A close association of yield with CAP and LAI at mid-grain filling was observed. In conclusion, for the tested growing conditions, decreasing the row spacing to an optimal distance (15 cm) maintained a longer duration of LAI and CAP during grain filling, made a better coordination of group and individual leaf photosynthesis, and accumulated higher aboveground biomass, leading to a greater grain yield. In addition, Wennong6 had a more rational canopy architecture than Jimai22 (improved LT and higher LAI) and CAP under 15-cm row spacing, leading to a higher grain yield, which indicated that the large-spike type cultivar has the potential to obtain higher yields by increasing plant density through optimum row spacing allocation (15 cm).